2016
DOI: 10.1890/15-2251.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating harvest‐based control of invasive fish with telemetry: performance of sea lamprey traps in the Great Lakes

Abstract: Physical removal (e.g., harvest via traps or nets) of mature individuals may be a cost-effective or socially acceptable alternative to chemical control strategies for invasive species, but requires knowledge of the spatial distribution of a population over time. We used acoustic telemetry to determine the current and possible future role of traps to control and assess invasive sea lampreys, Petromyzon marinus, in the St. Marys River, the connecting channel between Lake Superior and Lake Huron. Exploitation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Holbrook et al. (, this issue) further showed that sea lamprey abundance may have been underestimated in the St. Mary's River, suggesting that traps and sterilization were less successful at population control than previously assumed. Bacheler et al.…”
Section: Applicationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Holbrook et al. (, this issue) further showed that sea lamprey abundance may have been underestimated in the St. Mary's River, suggesting that traps and sterilization were less successful at population control than previously assumed. Bacheler et al.…”
Section: Applicationsmentioning
confidence: 95%
“…Holbrook et al. (, this issue) tracked the movements of invasive sea lamprey in the Great Lakes ecosystem, which are responsible for the extirpation of many native fishes, and evaluated the performance of lamprey traps as a means for their eventual removal and ecological mitigation. Raby et al.…”
Section: The Special Issue and Future Directionsmentioning
confidence: 99%
“…Previous research has not revealed any evidence that transport of adult sea lampreys among streams influence their behavior (Kelso et al 2001). To minimize possible violations of Assumption 1, we used the earliest-caught (i.e., least mature) lampreys from Lake Erie tributaries and used smaller transmitters than have been used on sea lampreys (Kelso and Gardner 2000;Holbrook et al In Press). Transmitter retention rates (Assumption 2) were perfect and failure rates were low (<3 %) in a recent study that used transmitters from the same manufacturer over a similar time period (Holbrook et al In Press), suggesting that violations of Assumption 2 were negligible.…”
Section: Assumptionsmentioning
confidence: 99%
“…Although control is not always an option, the costs of inaction can justify management programs to reduce the negative consequences of aquatic invasive species on ecosystems and the economies they support (Homans & Smith, ; Horsch & Lewis, ; Lovell, Stone, & Fernandez, ). In some freshwater systems, invasive species management has been performed through targeted removal during periods when individuals aggregate, including early developmental stages and adult migration (Bajer, Chizinski, & Sorensen, ; Holbrook et al, ).…”
Section: Introductionmentioning
confidence: 99%